Respiratory Disease and Infection A New Insight - Mahboub, Bassam H. (IntechOpen, 2013)
Medicine is an ever-changing science. Every day we are encountered with the new developments and knowledge in the pathogenesis, mechanism of disease, newer diagnostic modalities, treatment options and new challenges in the management of the various diseases. The same holds true for respiratory diseases with the emergence of new respiratory pathogens having significant impact on the respiratory system. Respiratory Diseases are an important contributor to the morbidity and mortality of mankind since antiquity and its prevalence is on rise in with new disease are being recognized, however little importance has been given to the respiratory disease due to low level of awareness in physicians and general public. This book has been designed to deliver the detailed knowledge about the various respiratory infections including viral, bacterial, and helminthic infections.